Analysis of Strategy Development at Increasing Sales Volume of Bright Gas 5.5kg Product Based on LPG Non PSO Agent Perception at PT. Pertamina Persero MOR V Denpasar Branch Office in Bali Province - PUTRA, I MADE ADI SUARDANA (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objective of this research is to analyze SWOT based on consumer perception for Bright Gas 5.5kg product at PT. Pertamina Persero Denpasar Branch Office MOR V Bali Province to obtain the development of strategy at functional level in an effort for increasing sales volume. This study used a descriptive method and collected data through interviews, observation, and documentation. Analysis techniques used in this study is SWOT analysis, SWOT matrix, and SWOT quantitative assessment according to O.C. Ferrel. The finding shows that Bright Gas 5.5kg product recommended for an aggressive marketing strategy. Implementation activity such as the creation of full service channel of Bright Gas 5.5kg, socialization on government workers, and makings event or sponsorship. Implementation of such strategies must be impulsive and uninterrupted. Therefore, Pertamina might use external resources so that the implementation of Bright Gas 5.5kg strategy could continuesly active.Â KEYWORDS: strategy analysis, SWOT, O.C. Ferrel, consumer perception, agresive strategy, implementat